Non-vanillyl resiniferatoxin analogues as potent and metabolically stable transient receptor potential vanilloid 1 agonists - Choi, Hyun-Kyung (2008)
A series of non-vanillyl resiniferatoxin analogues, having 4-methylsulfonylaminophenyl and fluorophenyl moieties as vanillyl surrogates, have been investigated as ligands for rat TRPV1 heterologously expressed in Chinese hamster ovary cells. Although lacking the metabolically problematic 4-hydroxy substituent on the A-region phenyl ring, the compounds retained substantial agonist potency. Indeed, the 3-methoxy-4-methylsulfonylaminophenyl analog (1) was modestly (2.5-fold) more potent than RTX, with an EC(50) = 0.106 nM. Further, it resembled RTX in its kinetics and pattern of stimulation of the levels of intracellular calcium in individual cells, as revealed by imaging. Compound 1 displayed modestly enhanced in vitro stability in rat liver microsomes and in plasma, suggesting that it might be a pharmacokinetically more favorable surrogate of resiniferatoxin. Molecular modeling analyses with selected analogues provide evidence that the conformational differences could affect their binding affinities, especially for the ester versus amide at the B-region.